Pemanfaatan Limbah Media Jamur Merang sebagai Pupuk Organik Tanaman Kangkung Darat (Impomea reptansPoir) untuk Mendukung Pertanian Berkelanjutan - Siti Wahana; Mutia Intan Savitri Herista; Ismail Saleh (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Aim from this research is to know about affect dosage of mushroom fertilizer to growht of kale land. The use of compost in planting kale land is one of the efforts to support sustainable agriculture. This research conduct in Trial Garden Gedung Tambahan Agriculture Faculty of Universitas Swadaya Gunung Jati. This reasearch conduct in Mei – July 2020. This research used Completely Randomized Design consisting of one factor. The factor is compost dosage with five treatment. There is 0 fertilizer : 4 soil, 1 fertilizer : 3 soil, 2 fertilizer : 4 soil, 3 fertilizer : 1 soil and 4 fertilizer : 0 soil. Every treatment repeat three times. The results showed that the difference in compost dosage significantly affected all growth vegetative parameters measured. The dose of K3 compost (3 compost: 1 soil) is the most optimal for the vegetative growth of kale. dry weight the most appropriate dose is K4 compost (4 Compost : 0 soil).